Speed-accuracy tradeoff of fingertip force control with visual/audio/haptic feedback. Issue 110 (February 2018) - Li, Teng; Wang, Dangxiao; Peng, Cong; Yu, Chun; Zhang, Yuru
Highlights: Fingertip force control process obeyed Fitts' law in each single sensory modality (visual/audio/haptic) when the difficulty level was within a specific range. The response time in the audio feedback mode was the shortest among the three feedback conditions while that in the haptic feedback mode was the longest. The Linear model has the best fit in all three feedback modes among all three models. Abstract: Fitts' law has been widely used in the human-computer interaction (HCI) field, especially for Graphical User Interface (GUI) design. However, most studies on Fitts' law were performed with motion control tasks under visual feedback while only a few endeavor to measure human force control behavior. How quickly humans can exert a constant force with a required accuracy and whether this speed-accuracy tradeoff obeys Fitts' law still needs to be explored. In this paper, human capabilities for controlling absolute magnitudes of fingertip force with discrete visual/audio/haptic feedback cues were observed and compared. Eighteen participants applied constant forces by pressing a force sensor with their index fingers in the three feedback modes respectively. Response time of 24 pairs (4 × 6) of Magnitude-Tolerance conditions were measured. The results showed that the response time obeyed Fitts' law within a certain range of force accuracy in all the three feedback modes, while the Linear speed-accuracy tradeoff model was almost superior for the force control process than the Meyer formulation and the Shannon formulation. The response time in the audio feedback mode was the shortest among the three feedback conditions. The results may be used as guidelines for applications that rely on accurate and quick force control under different feedback conditions such as fast tapping tasks on a touch screen.